The impact of the evaluations made by Mini-CEX on the clinical competency of nursing students - Sanaz Motefakker; Azam Shirinabadi Farahani; Manijeh Nourian; Maliheh Nasiri; Fatemeh Heydari (BMC Medical Education, 2022)
Abstract Introduction Clinical competency is defined as one’s capabilities in terms of knowledge, attitude and practice, and is a necessity for nursing practice. Evaluation is the inseparable part of the education process, without which the quality of education could not be measured. Considering the characteristics of clinical education and its impact on the clinical competency of students, as well as the importance of making precise evaluations of them using scientific, modern and efficient approaches, this study aims to investigate the impact of the evaluation made using Mini-Clinical Evaluation Exercise on the clinical competency of the nursing students of the School of Nursing and Midwifery Shahid Behesti University. Methods This is a quasi-experimental study with a control group conducted on students who were taking courses “Nursing care for a sick child”. The students were classified into the intervention and control groups using complete enumeration. The evaluations were made using Mini-Clinical Evaluation Exercise in the intervention group and the portfolio approach in the control group. The skills regarding patient (mother–child) education, IV therapy and medication were evaluated by checklists. Findings The results showed that the mean score of clinical competency in the intervention group was significantly higher than that of the control group. Conclusion Considering the improvement of clinical competency in the intervention group, it is recommended to use Mini-Clinical Evaluation Exercise for the evaluation of students.